Novel (p)ppGpp Binding and Metabolizing Proteins of Escherichia coli - Zhang, Yong; Zborníková, Eva; Rejman, Dominik; Gerdes, Kenn (mBio, 2018)
The alarmone (p)ppGpp plays pivotal roles in basic bacterial stress responses by increasing tolerance of various nutritional limitations and chemical insults, including antibiotics. Despite intensive studies since (p)ppGpp was discovered over 4 decades ago, (p)ppGpp binding proteins have not been systematically identified in Escherichia coli We applied DRaCALA (differential radial capillary action of ligand assay) to identify (p)ppGpp-protein interactions. We discovered 12 new (p)ppGpp targets in E. coli that, based on their physiological functions, could be classified into four major groups, involved in (i) purine nucleotide homeostasis (YgdH), (ii) ribosome biogenesis and translation (RsgA, Era, HflX, and LepA), (iii) maturation of dehydrogenases (HypB), and (iv) metabolism of (p)ppGpp (MutT, NudG, TrmE, NadR, PhoA, and UshA). We present a comprehensive and comparative biochemical and physiological characterization of these novel (p)ppGpp targets together with a comparative analysis of relevant, known (p)ppGpp binding proteins. Via this, primary targets of (p)ppGpp in E. coli are identified. The GTP salvage biosynthesis pathway and ribosome biogenesis and translation are confirmed as targets of (p)ppGpp that are highly conserved between E. coli and Firmicutes In addition, an alternative (p)ppGpp degradative pathway, involving NudG and MutT, was uncovered. This report thus significantly expands the known cohort of (p)ppGpp targets in E. coliIMPORTANCE Antibiotic resistance and tolerance exhibited by pathogenic bacteria have resulted in a global public health crisis. Remarkably, almost all bacterial pathogens require the alarmone (p)ppGpp to be virulent. Thus, (p)ppGpp not only induces tolerance of nutritional limitations and chemical insults, including antibiotics, but is also often required for induction of virulence genes. However, understanding of the molecular targets of (p)ppGpp and the mechanisms by which (p)ppGpp influences bacterial physiology is incomplete. In this study, a systematic approach was used to uncover novel targets of (p)ppGpp in E. coli, the best-studied model bacterium. Comprehensive comparative studies of the targets revealed conserved target pathways of (p)ppGpp in both Gram-positive and -negative bacteria and novel targets of (p)ppGpp, including an alternative degradative pathway of (p)ppGpp. Thus, our discoveries may help in understanding of how (p)ppGpp increases the stress resilience and multidrug tolerance not only of the model organism E. coli but also of the pathogenic organisms in which these targets are conserved.
Keywords: Protein Binding; multidrug tolerance; vazba proteinů; Escherichia coli Proteins; GTPase; DRaCALA; proteiny z Escherichia coli; Gene Expression Regulation, Bacterial; (p)ppGpp; Escherichia coli; Guanosine Tetraphosphate; Guanosine Pentaphosphate; guanosintetrafosfát; Nudix; regulace genové exprese u bakterií; guanosinpentafosfát; persistence